Long-term follow-up data more than 5 years after surgical management of benign prostate obstruction: who stands the test of time?. Issue 1 (January 2016) - Rieken, Malte; Bachmann, Alexander; Shariat, Shahrokh F.
Abstract : Purpose of review: Surgical techniques are an integral part of the urologist's armamentarium for the treatment of benign prostatic obstruction. Currently, several techniques are available. The purpose of the current review is to analyse the long-term outcomes of currently available techniques. Recent findings: Open prostatectomy shows a low long-term reoperation rate. Available evidence suggests that bipolar transurethral resection of the prostate (TURP) is an attractive alternative to monopolar TURP as both techniques lead to a long-lasting and comparable efficacy. For patients with a larger prostate volume, bipolar enucleation of the prostate appears as safe and effective alternative to open prostatectomy. Holmium laser enucleation of the prostate appears as a durable alternative to TURP and open prostatectomy with comparable long-term results. For photoselective vaporization of the prostate, differently powered models are available. Currently, only long-term data with lower powered 80 W laser are available, reporting reoperation rates higher than those reported from other surgical techniques. On the thulium laser, currently only one study reported 5-year results and despite encouraging results further confirmation seems necessary. Summary: Various surgical methods have proven to be safe and effective for the treatment of benign prostate obstruction and stand the test of time. The choice of the technique depends on prostate size, risk factors of the patient as well as expertise of the surgeon.